Geochemical and sedimentological record of sediment core PHE1 retrieved from the Pheneos Polje (Peloponnese, Greece) - Joana Seguin; Pavlos Avramidis; Annette Haug; Torben Kessler; Arndt Schimmelmann; Ingmar Unkel (PANGAEA, 2020)
The sediment core PHE1 (37.85114° N, 22.33510° E) was retrieved from the eastern bay of the Pheneos Polje, Peloponnese Greece, in spring 2017 using a piston corer (Stitz type). The sedimentary sequence covers 390 cm (sedimentary units 1 - 9). The core was scanned at 0.5 cm resolution with an Avaatech X-ray Fluorescence (XRF) core scanner and the raw data presented here is displayed as element counts per second (cps). RGB colour values were taken with a digital line scan camera to depict colour variation with depth. The concentrations of total nitrogen (TN), total organic carbon (TOC), and total inorganic carbon (TIC) were determined on dried, grinded, and homogenized samples through combustion in an elemental analyzer (Euro EA, Elementanalyzer). The grain size distribution <2 mm was measured on air-dried samples (ca. 0.3 g) using a laser-particle-analyser Malvern Mastersizer 2000. The core sequence covers the largest part of the Holocene and was analysed to reconstruct ecosystem and landscape changes as well as palaeoclimatic fluctuations in southern Greece.